Four Kinds of Perspectival Truth. (10th June 2016) - Massimi, Michela
Abstract : In this paper, I assess recent claims in philosophy of science about scientific perspectivism being compatible with realism. I clarify the rationale for scientific perspectivism and the problems and challenges that perspectivism faces in delivering a form of realism. In particular, I concentrate my attention on truth, and on ways in which truth can be understood in perspectival terms. I offer a cost‐benefit analysis of each of them and defend a version that in my view is most promising in living up to realist expectations.